ORBIS as a Research Tool: Examination of the Capital Structure of the Hungarian and French Wine Industry - Martin Luptak; Daniel Boda; Gabor Szucs (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
ORBIS is a global database and financial analysis tool offering company statements, ownership, rating and scores, news and intelligence. Global means the current coverage exceeds 165 million entities which most of them are private companies. However also listed companies, banks (over 35.000), insurance companies are included. And all that taking into consideration how different the legislations in countries are sometimes not only giving the free choice to companies when it comes to publish the reports but also forbids to do so (some Islamic jurisdictions). Goal of the paper is to demonstrate the usage of ORBIS in the examination of the capital structure of the Hungarian and French wine industry.
Keywords: G32; C30; 330; ORBIS; capital structure; wine industry; discriminant analysis; profitability